PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN COOPERATIVE SCRIPT SISWA KELAS XI MIPA 1 MAN 1 TULUNGAGUNG - Sri Munfarida (Universitas Bhinneka PGRI, 2023)
Mathematics is a common science underlying the development of modern technology, has an important role in various disciplines and advance the human mind. Cooperative learning in terms of learning gotong royong, the learning system that provides opportunities for learners to work with other students in structured tasks. Furthermore it is said, cooperative learning only runs when a group or a team is formed in which students work directed to achieve goals that have been determined by the number of group members in general consists of 4-6 people only. This study is planned in two cycles and each cycle is done daily. As the subjects in this study are students of class XI MIPA 1 MAN 1 Tulungagung academic year 2021/2022 with the number of students as many as 33 people. The data in this research were collected by using observation sheet and test of mathematics learning result of the students. Observations made by the researchers themselves on the activities of students and teachers during the learning process, for each meeting by filling out the observation sheet that has been provided. In cycle I, teacher activity is still not maximal in applying the model of study being studied. It can be seen the parts that have not been implemented by the teacher in the learning process in accordance with the Cooperative Script learning model, ie the teacher is less in conveying the learning objectives, the teacher is still not guiding the students in doing the UKBM and less in the timing so that all activities in plan has not been done properly. The level of student activity in cycle I has increased, although not yet optimal. Students have started to follow the learning well, are willing to discuss with friends of the group, even students want to ask the teacher about the material that has not been understood. It also has an impact on improving student learning outcomes. In the first cycle, student learning outcomes increased to 30% from 60% before the action. In cycle II, teacher activity can be said to be maximal, due to an increase in the done by the teacher. The existence of reflection from cycle I, make teachers begin to improve its performance. This can be seen from the activity of teachers who are in accordance with what is planned. In cycle II, students have started to be active in learning and cooperation in the group the better. So that the result of learning mathematics of student also increase by applying Cooperative Script learning model from mean of student pre-action score.